Confessing and believing : the Apostles' Creed as script for the Christian life - Hart, Trevor (1517 Media, 2022)
Confessing and Believing offers a faithful and compelling account of the Christian faith using the Apostles' Creed as a framework. In this book Trevor Hart helps readers, both within and outside the church, understand core Christian beliefs, and how these are related to one another and to the intellectual and cultural contexts of today.